Metalloneurochemistry and the Pierian Spring: 'Shallow Draughts Intoxicate the Brain'. Issue 9 (29th July 2016) - Goldberg, Jacob M.; Loas, Andrei; Lippard, Stephen J.
Abstract: Metal ions perform critical and diverse functions in nervous system physiology and pathology. The field of metalloneurochemistry aims to understand the mechanistic bases for these varied roles at the molecular level. Here, we review research that illustrates progress toward achieving this ambitious goal and identify key challenges for the future. We examine the use of lithium as a mood stabilizer, the roles of mobile zinc and copper in the synapse, the interplay of nitric oxide and metals in retrograde signaling, and the regulation of iron homeostasis in the brain. We are beginning to uncover the principles by which receptors and transmitters utilize metal ions to modulate neurotransmission. These advances have revealed exciting new insights into the intricate mechanisms that give rise to learning, memory, and sensory perception, while opening many new avenues for further exploration. Abstract :